Intent in Islamic Law : Motive and Meaning in Medieval Sunnī Fiqh - Powers, Paul (Brill Book Archive Part 1, ISBN: 9789004472495., 2005)
This book explores the nature and role of intent in pre-modern Islamic legal rule books, including ritual, commercial, family, and penal law. It argues that Muslim jurists treat intent as a definitive element of many actions regulated by the Shari'a, and they employ a variety of means and terms to assess and categorize subjective states. Through detailed analyses of medieval Islamic texts, aided by Western philosophical examinations of intent, the author presents technically detailed yet lucid arguments about Islamic religious ritual and spirituality, the ethics of business transactions, the role of the inner self in crime and punishment, and Muslim understandings of agency and language. This is the first extensive exploration of the crucial legal issue of intent in all major areas of Islamic substantive law.